Predicting Peer Nominations Among Medical Students: A Social Network Approach. (June 2016) - Michalec, Barret; Grbic, Douglas; Veloski, J. Jon; Cuddy, Monica M.; Hafferty, Frederic W.
Abstract : Purpose: Minimal attention has been paid to what factors may predict peer nomination or how peer nominations might exhibit a clustering effect. Focusing on the homophily principle that "birds of a feather flock together, " and using a social network analysis approach, the authors investigated how certain student- and/or school-based factors might predict the likelihood of peer nomination, and the clusters, if any, that occur among those nominations. Method: In 2013, the Jefferson Longitudinal Study of Medical Education included a special instrument to evaluate peer nominations. A total of 211 (81%) of 260 graduating medical students from the Sidney Kimmel Medical College responded to the peer nomination question. Data were analyzed using a relational contingency table and an ANOVA density model. Results: Although peer nominations did not cluster around gender, age, or class rank, those students within an accelerated program, as well as those entering certain specialties, were more likely to nominate each other. The authors suggest that clerkships in certain specialties, as well as the accelerated program, may provide structured opportunities for students to connect and integrate, and that these opportunities may have an impact on peer nomination. The findings suggest that social network analysis is a useful approach to examine various aspects of peer nomination processes. Conclusions: The authors discuss implications regarding harnessing social cohesion within clinical clerkships, the possible development of siloed departmental identity and in-group favoritism, and future research possibilities.